Study of Students' Knowledge about Bokashi Fertilizer, Its Benefits for Plants, and Science Education Students' Perspectives on Its Use in Society - Fitriyadi, Muhammad; Vebrianto, Rian; Hariman, Faisal; Berlian, Mery (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Understanding the environment and natural resource management is very important for science students because it can support the application of sustainability principles in everyday life. This study aims to describe the knowledge and understanding of science education students at Sultan Syarif Kasim State Islamic University, Riau, about the use of bokashi fertilizer in sustainable agriculture. The research design used is cross-sectional research, which is a type of descriptive research to describe the characteristics or phenomena that exist in the population. The sample in this study was selected randomly using a simple sampling technique, with the number of samples adjusted to the inclusion criteria. Data collection was carried out using a questionnaire consisting of closed and open questions designed to explore students' knowledge about bokashi fertilizer, its ecological benefits, and students' views on the application of this fertilizer in agricultural practices. The data obtained were then analyzed descriptively to describe the level of students' knowledge and attitudes towards bokashi fertilizer. Statistical analysis was carried out by calculating the frequency and percentage of each variable measured. The respondents in this study were students majoring in science education at Sultan Syarif Kasim State Islamic University, Riau. Based on the results of the recorded knowledge evaluation, a value of 69.1% was obtained with a category of strongly agreeing with the statement that the use of bokashi fertilizer can fertilize plants. Regarding the benefits of the activity, a value of 50.9% was obtained with the category of benefits of this program for sustainable agriculture. Based on the results of this study, it is recommended to increase socialization about the benefits of bokashi fertilizer to students and the community. In conclusion, Science students have a fairly good understanding of the benefits of bokashi fertilizer, especially in terms of increasing soil fertility and reducing the negative impacts of using chemical fertilizers.